Anidación de la avifauna en vaciante en la Comunidad Claverito a orillas del río Itaya. Loreto.Perú - Cubas Poclin De Saboya, Susana (2023)
With the objective to know about avifauna’s nesting, this study was realized in the community of Claverito on the banks of the Itaya river, Iquitos-Loreto. To know the nesting, nest search techniques were used during the construction, laying, incubation and rearing of chicks, besides, the support plants of the nests were described. 14 species of birds nesting in 122 nests were recorded, the most representative families were Thraupidae and Icteridae, the species with the highest number of nests were Chrysomus icterocephalus (n=34) and Leistes militaris (n=26). 8 species of support plants belonging to the grass, shrub and tree habits were recorded, the most representative families were myrtaceae and poaceae. Regard to the nests, the lengths and heights varied from 7 x 6 in Volatinia jacarina to 45.6 cm in Certhiaxis mustelinus, the most common shapes were bowl, platform and rounded, the natural construction material stood out with respect to the mixed one. Regarding the eggs, the oval shape stood out from the rest (n=8), the eggs of Leistes militaris presented different shapes oval, elliptical and pyriform; clutch ranged from 1 to 4 eggs, ground color ranged from white to light blue; markings on eggs were located mostly on the crown, markings were recorded in 5 species and varied from variegated, spotted, scribbled, mottled to dotted. Finally, the number of chicks per nest varied from 1 in Todirostrum maculatun and Nyctidromus albicollis to 4 in Leistes militaris, the predominant beak color was grey, and the skin varied between yellow and grey. In conclusion, the number of bird species that nest in a certain place could be influenced by the type of habitat and the plants with characteristics required by the bird species.